Food Safety in the Thematic Interpretation of the Qur'an - Albanna, Mohammad Rifât (UIN Sunan Gunung Djati Bandung, 2025)
Food security is a multidimensional global challenge with material, spiritual, and social aspects. This research explores the concept of food security in the Al-Qur'an through a thematic (maudu’i) tafsir approach, analyzing relevant verses to understand its principles and applications. The study identifies the concept of food security in the Qur'an, analyzes its principles based on Qur'anic verses, explains the roles of individuals, families, and society in supporting food security, and examines related challenges based on thematic interpretations of the Qur'an. Using a qualitative method with literature study and thematic interpretation, the research analyzes Al-Qur'an verses through authoritative tafsir books supported by related literature. The results show that the Qur'an emphasizes a holistic concept of food security with spiritual, social, and material dimensions, stressing sustainability, fair distribution, and ecosystem balance. Principles include sustainable resource management, strategic planning, and distributive justice. The responsibility lies with individuals consuming halal, families ensuring welfare, and society supporting fair distribution. Key challenges identified are resource exploitation, unequal distribution, and climate change.